2005
DOI: 10.1097/01.mlg.0000150679.60731.bc
|View full text |Cite
|
Sign up to set email alerts
|

Gastrostomy Tubes in Patients with Advanced Head and Neck Cancer

Abstract: Although clinical judgment appears to be sufficient for deciding when G-tube placement is warranted in our population, the threshold for placing a tube should be lower in those patients who had a higher likelihood of requiring a G-tube during the course of treatment, including those with advanced disease of the oral cavity, oropharynx, and hypopharynx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…3,4,15 Our findings were concordant with these studies except that we did not find a significant relationship between hypopharyngeal tumors and G-tube placement, presumably because most surgeries for hypopharyngeal cancer involve a laryngopharyngectomy, which rarely results in swallowing dysfunction. We also found that larger tumors (ie, T3-T4) were more likely to require postoperative G-tubes, which is intuitive, given the greater volume of tissue excised with larger tumors and the need for larger and potentially more bulky reconstructions.…”
Section: Discussionsupporting
confidence: 89%
“…3,4,15 Our findings were concordant with these studies except that we did not find a significant relationship between hypopharyngeal tumors and G-tube placement, presumably because most surgeries for hypopharyngeal cancer involve a laryngopharyngectomy, which rarely results in swallowing dysfunction. We also found that larger tumors (ie, T3-T4) were more likely to require postoperative G-tubes, which is intuitive, given the greater volume of tissue excised with larger tumors and the need for larger and potentially more bulky reconstructions.…”
Section: Discussionsupporting
confidence: 89%
“…Finding dose/volume predictors of PEG insertion during treatment may help to identify the subgroup of patients in whom the benefits of supportive care and nutritional support intervention are maximized when delivered in a timely fashion (12,13). Moreover, for the majority of patients who will not need a PEG tube during treatment, their application has the potential to reduce the incidence and the severity of both acute and consequential late side effects, such as longterm dysphagia (11).…”
Section: Discussionmentioning
confidence: 99%
“…Another concern would be the potential for enhanced risk of atrophy of the masticatory and swallowing muscles, resulting in long-term feeding tube dependence (11). Therefore, timely identification of the subgroup of patients who will require a PEG tube during treatment is critical to maximize its benefits (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with advanced neoplasm of the head and neck require special attention, because they present significant deterioration of their quality of life, mainly owing to the location of these tumors, which, when invasive, can affect the swallowing function, with direct consequences on the nutritional status and survival of these individuals (11) . However, the difficulty in maintaining adequate ingestion of nutrition is a consequence not only of the neoplasm but also of the treatment used, which varies from extensive resection of the oropharynx to chemotherapy and radiotherapy.…”
Section: Indicationsmentioning
confidence: 99%